Role of Dead Space in the Development and Diagnosis of Respiratory Failure - Ye. M. Levite; A. N. Uklonsky; V. F. Kulakov (Общая реаниматология, 2009)
The volumes of the dead space (anatomic and alveolar) play an important role in the physiology of external respiration and information on these volumes makes the diagnosis of different respiratory disorders easier. The volume of the anatomic dead space (the last inspiratory portions) is uninvolved in the mixing with the gas of functional residual capacity (FRC) and leaves the airways unchanged in the gas composition on expiration. Mixing of the other portion of the tidal volume with FRC gas should be regarded as preparation for an alveolar gas exchange process. The increased partial value of the anatomic dead space in the tidal volume with its decrease (tachypnea) and, accordingly, reduced alveolar ventilation volume may result in ventilation respiratory failure. The time course of changes in the volume of the alveolar dead space is easily detectable from the decrease in expiratory CO2 concentrations as compared with PaCO2. The increased alveolar dead space volume suggests impaired local blood flow (thromboembolism, acute respiratory distress syndrome) in the lesser circulation and gives grounds to diagnose shunting and venous mixing. Procedures for measuring the dead space volumes are simple and may be introduced into clinical practice. Key words: anatomic dead space, alveolar dead space, functional residual capacity, respiratory failure.